Teachers' Efforts In Shaping Students' Critical Thinking Skills In Learning At The Madrasah Ibtidaiyah Level - Atiq Yufitriyah Uswah; Mukni’ah Mukni’ah; Abd. Muhith; Zulfia Al Qorina; Litsa Nailul Fauziah (Institut Agama Islam An-Nawawi Purworejo, 2024)
This study examines teachers' efforts in improving students' critical thinking skills at the Madrasah Ibtidaiyah level. Through qualitative methods and case studies, research involves teachers and students as subjects. Data were collected through qualitative research methods. The findings show that Madrasah Ibtidaiyah Country 5 Jember teachers use various ways to encourage students' critical thinking skills, such as critical questions, discussions, selection of relevant material, feedback, and critical thinking tasks. Teacher-student interaction and student empowerment through projects also have a positive impact. The conclusion of this study confirms that the role of teachers is very important in shaping the critical thinking skills of Madrasah Ibtidaiyah students. The implication is that curriculum development and teacher training need to pay attention to effective strategies in stimulating critical thinking skills. These findings provide insight for the development of education in Madrasah Ibtidaiyah Country 5 Jember, emphasizing the importance of critical thinking skills as an integral part of learning.